Social Engineering for Ethical Dilemma about Anti-Corruption Intellectual Consciousness - Wahyu Prananta, Arie; Siahaan, Hotman (International Journal of Engineering and Technology, 2018)
This study aims to find that high integrity is to break away from personal roles and public roles, starting with the selection of places they develop intellectuals in the anti-corruption movement. So they choose a place that can accommodate the minds of those who are anti-mainstream and dare to get out of their comfort zones and enter into a system to change the system, even though at risk they will become isolated individuals, unpopular and always in a separate space. For those who from the beginning chose the area of power and politics gave rise to two groups of intellectuals, namely the group that still wishes to carry out anti-corruption thinking and groups that merge into corruptors. The ethical dilemma for groups in the area of the anti-corruption movement is lighter because the ethical dilemma is in his role. While the groups in the field of power and politics are more massive because some can only see and experience extraordinary shock until stressed but cannot report it, some others fall into the world of corruption.Â Â